Tribotechnical characteristics of gas-thermic spraying coating with different types of hardening - Остраниця, Г. Є.; Назаренко, П. В.; Поліщук, І. Є. (Proceedings of National Aviation University (archive), 1998)
The triboengineering characteristics of gas-thermal spraying coating with different types of hardening in friction in respect to bronze have been examined. It has been established that high level of it corresponds to formation of heterogeneous secondary structures of the mixed type on the coatings. The coatings, based on Ni, after intermetallide hardening have better properties than coatings based on Fe-Ni, containing the phases of penetration MeC